Assessing urban recreation ecosystem services through the use of geocache visitation and preference data: a case-study from an urbanised island environment - Mario V Balzan; Iain Debono (One Ecosystem, 2018)
Recreation is an important cultural ecosystem service and is one way in which communities experience the direct and indirect benefits arising from the experiential use of their environment. The recent rise in popularity of Global Positioning System (GPS) game applications, which combine information technology with an activity that increases mobility and encourages outdoor enjoyment, provides ecosystem service practitioners with an opportunity to make use of this georeferenced data to assess recreational ecosystem services. Geocaching is one such worldwide outdoor game. It has fixed points of incursion where people can hide and look for caches. This study explores the possibility of using geocaching data as a proxy for recreational ecosystems services in the Maltese Islands. A quantitative analysis of the georeferenced caches was used together with their visit rates and number of favourite points. This was supplemented by two questionnaires that investigated the preferences and experiences of both geocache placers (n=39) and hunters (n=21). Results show that the highest number of caches were placed and searched for in urban areas and that geocaching is strongly associated with the presence and accessibility of urban green infrastructure. The number of geocachers who stated preference for experiences in nature did not translate into high visit rates to sites of high conservation value (protected areas) but landscape value was significantly associated with recreational ecosystem services flow. The results presented here provide evidence that geocaching spatial data can act as an indicator for assessing and mapping recreational ecosystem services in urban environments and in cultural landscapes.